1995
DOI: 10.1007/bf01744901
|View full text |Cite
|
Sign up to set email alerts
|

The arrhythmogenic right ventricle. Dysplasia versus cardiomyopathy

Abstract: Twenty-four patients presenting with arrhythmogenic right ventricular dysplasia/cardiomyopathy (ventricular tachycardia of right ventricular origin associated with structural abnormalities of the right ventricle) were divided into two groups with left ventricular ejection fraction (LVEF) above or below 45%. The distribution of LVEF in the group with LVEF below 45% was comparable with the distribution in 6 patients with idiopathic dilated cardiomyopathy who had ventricular tachycardia originating in the left ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…The large percentage of cases of fibrofatty ARVC in the present study supports the concept that in many cases, fibrofatty ARVC is an end stage of a remote inflammatory process, with increased cell death possibly due to apoptosis. 15 However, this study does not rule out the possibility that inflammation is a superimposed process, as favored by Fontaine et al 16 It remains to be proven whether fibrofatty ARVC is ever the result of a previous viral infection, as molecular studies for enteroviral RNA suggest in a small proportion of cases of idiopathic dilated cardiomyopathy. 17 The present study demonstrates that with extensive sampling of the left ventricular myocardium, fibrofatty replacement of the epicardium may be found in a majority of cases of fibrofatty ARVC.…”
Section: Fibrofatty Arvcmentioning
confidence: 73%
“…The large percentage of cases of fibrofatty ARVC in the present study supports the concept that in many cases, fibrofatty ARVC is an end stage of a remote inflammatory process, with increased cell death possibly due to apoptosis. 15 However, this study does not rule out the possibility that inflammation is a superimposed process, as favored by Fontaine et al 16 It remains to be proven whether fibrofatty ARVC is ever the result of a previous viral infection, as molecular studies for enteroviral RNA suggest in a small proportion of cases of idiopathic dilated cardiomyopathy. 17 The present study demonstrates that with extensive sampling of the left ventricular myocardium, fibrofatty replacement of the epicardium may be found in a majority of cases of fibrofatty ARVC.…”
Section: Fibrofatty Arvcmentioning
confidence: 73%
“…2,[3][4][5]18,19 This view is reinforced by the present finding that younger age is an independent risk factor for ventricular fibrillation/flutter. Fontaine et al 20 reported a bimodal distribution of left ventricular ejection fraction in ARVC/D patients, with mean values of 58% and 25%, respectively, and advanced the hypothesis that this pattern was accounted for by a superimposed factor, such as acute myocarditis leading to hemodynamic deterioration of the left ventricle. The subgroup of patients with severe left ventricular dysfunction showed an increased mortality rate due to congestive heart failure.…”
Section: Risk Predictors and Indications For Icd Implantmentioning
confidence: 92%
“…On the other hand, the absence of PKP2 mutations in nonfamilial ARVC cases suggests the possibility of a nongenetic origin, eg, myocarditis or alternatively a spontaneous mutation in another gene. 38,39 Finally, all 5 index patients with familial ARVC and sudden death in family members Ͻ35 years of age appeared to be PKP2 mutation carriers.…”
Section: Genotype-phenotype Relationshipsmentioning
confidence: 92%